Why Do Partisan Media Polarize Viewers?. Issue 3 (26th February 2013) - Levendusky, Matthew S.
<x xml:space="preserve">Abstract</x> The recent increase in partisan media has generated interest in whether such outlets polarize viewers. I draw on theories of motivated reasoning to explain why partisan media polarize viewers, why these programs affect some viewers much more strongly than others, and how long these effects endure. Using a series of original experiments, I find strong support for my theoretical expectations, including the argument that these effects can still be detected several days postexposure. My results demonstrate that partisan media polarize the electorate by taking relatively extreme citizens and making them even more extreme. Though only a narrow segment of the public watches partisan media programs, partisan media's effects extend much more broadly throughout the political arena.